Array‐Based High‐Throughput Screening in Mouse Embryonic Stem Cells with shRNAs. (16th February 2018) - Wang, Chia‐Hui; Ma, Nianhan; Lin, Yu‐Tsen; Wu, Cheng‐Chung; Wu, Hong‐Jin; Yu, Ching‐Chia; Hsiao, Michael; Lu, Frank Leigh; Schuyler, Scott C.; Lu, Jean
ABSTRACT: High‐throughput short‐hairpin RNA (shRNA) lentivirus screening is a powerful tool for identifying multiple functional regulators in embryonic stem cells (ESCs). shRNA libraries can efficiently down‐regulate target genes persistently with high efficiency. The concurrent measurement of relative cell number by alamarBlue (AB) assay and undifferentiated ESC markers via an alkaline phosphatase (ALP) activity assay in the same cell culture well provides an efficient and economical way to pinpoint factors crucial for ESC pluripotency and/or expansion. Most of the renewal pathways affect ALP activity. Thus, multiple positive and negative regulators can be identified by this method. In addition, morphological changes and/or the expression levels of specific pluripotency or differentiation markers examined by immunofluorescence can be used as secondary screens for target‐gene selection. In summary, we describe an efficient way to identify multiple regulators of ESC renewal using shRNAs. Curr. Protoc. Stem Cell Biol . 26:5C.3.1‐5C.3.19. © 2013 by John Wiley & Sons, Inc.